Soybean yield, protein content and oil quality in response to interaction of arbuscular mycorrhizal fungi and native microbial populations from mono- and rotation-cropped soils - Marro, Nicolás; Cofré, Noelia; Grilli, Gabriel; Alvarez, Carolina; Labuckas, Diana; Maestri, Damián; Urcelay, Carlos (Elsevier, 2021)
Two main soil management practices are generally used for soybean production: monoculture (MC) and croprotation (CR). These strategies have different impacts on soil microbial communities. Among them, arbuscularmycorrhizal fungi (AMF) are well known to provide access to nutrients in a majority of cultivated plants. AMFcommunities have been shown to be more diverse in CR than in MC. Because AMF species differ in their effectson nutrition and development of plants, it could be expected that soil biota from different soil managementpractices affect soybean yield and quality. Therefore the objective of this study was to examine the combinedeffects of soil microbial communities and soil management practices (MC and CR) on yield, protein content, andoil quality of soybean grown under greenhouse conditions. The effects of three soil treatments, namely: sterile(S); microorganisms without AMF (MO); and microorganisms with AMF (AMF) were evaluated. These treatmentswere applied to soils from two crop management practices (CR and MC). Sterile soil promoted lower numbers ofpods and seed weight per plant in MC but not in CR. AMF showed increased seed protein content (12–14%)whereas MO presented increased oil concentration (20–27%) (mainly within CR). Soybean grown with AMFfrom CR soil showed significantly higher amounts of oleic acid (21–25%), and lower linoleic acid (9%) whencompared with other treatments. Findings from this study suggest that soybean yield and quality are affected bycrop management practices and soil biota composition. Further, these parameters should be considered at thetime of selecting agricultural strategies.